2011
DOI: 10.1080/15332586.2011.587381
|View full text |Cite
|
Sign up to set email alerts
|

On the Association Between SROs, Private Security Guards, Use-of-Force Capabilities, and Violent Crime in Schools

Abstract: Although school crime and the use of security measures to combat school crime has been the focus of a number of prior empirical studies, there is substantially less information known about the relationship between school resource officers (SROs) and private security guards in schools and school crime. Using data from the 2006 School Survey on Crime and Safety, this study investigates the relationships among school characteristics and school crime with a particular focus on their differential effects across sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SSOCS, a nationally representative sample of U.S. public schools, is considered one of the richest datasets for studies of school violence. Data from the SSOCS have been used in many published studies throughout the last decade (Chen, 2008;Granberg-Rademacker et al, 2007;Jennings et al, 2011;Kupchik & Ward, 2014;Maskaly, Donner, Lanterman, & Jennings, 2011;O'Neill & McGloin, 2007;Patton, 2011;Phillips et al, 2014). School administrators from elementary, middle, and high schools complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…These security variables have also been used in other studies of violence utilizing this database (GranbergRademacker et al, 2007;O'Neill & McGloin, 2007;Phillips et al, 2014). The SRO variable measures whether the school has a school resource officer employed at the school Maskaly et al, 2011).…”
Section: School Securitymentioning
confidence: 97%
See 2 more Smart Citations
“…However, evidence on the effectiveness of these programs has been inconsistent. Some studies have suggested that SRO programs reduce violence in schools (Carroll, Ben-Zadok, & McCue, 2010;Johnson, 1999;Maskaly, Donner, Lanterman, & Jennings, 2011). For instance, Johnson (1999) analyzed data from nine high schools and eighteen middle schools, revealing that overall school suspensions gradually decreased in both middle and high schools with the placement of police officers.…”
Section: Effectiveness Of Sro In Reducing Crime and Improving The Schmentioning
confidence: 99%